1, 3, 6-Trihydroxy-7-Methyl-9, 10-Anthracenedione Isolated from genus Lindera with Anti-Cancer Activity - Wei, Guoqing; Chen, Hui; Nie, Fangyuan; Ma, Xiaofeng; Jiang, Hezhong (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Natural products inhibiting fatty acid synthase are potential therapeutic agents to treat cancer. Objective: To investigate the chemical constituents of the root tubers of Lindera aggregate and the stems of Linderanacusua, and to find natural inhibitors on the expression level on fatty acid synthase in human breast cancer MDA-MB-231 cells. Methods: The isolation and purification of the extracts were conducted by the methods of percolation and partition extraction, silica and gel column chromatography, recrystallization and by NMR and spectroscopic analysis method. The cell viability was assessed by Cell Counting Kit assay. Results: Seven compounds were elucidated, mainly including five sesquiterpenes, one anthraquinoe and one γ -butanolide, in which compounds 6 was firstly reported from genus Lindera, and compound 7 was isolated from Linderanacusuafor the first time. Among them, 1,3,6-Trihydroxy-7-methyl-9,10-anthracenedione (TMA, compound 6) showed strong inhibitory effect on the expression level on fatty acid synthase in human breast cancer MDA-MB-231 cells. In addition, TMA was found to reduce breast cancer cells viability dosedependently. Conclusion: The fatty acid synthase was a potent therapeutic target for cancers, these findings suggest that TMA has the application potential for treating human cancers.
Keywords: Anthraquinone